Approaches and applications in transdermal and transpulmonary gene drug delivery - Zhang, Anni; Zhang, Xuran; Chen, Jiahui; Shi, Xianbao; Yu, Xijuan; He, Zhonggui; Sun, Jin; Sun, Mengchi; Liu, Zhijun (Frontiers in Bioengineering and Biotechnology, 2025)
Gene therapy has emerged as a pivotal component in the treatment of diverse genetic and acquired human diseases. However, effective gene delivery remains a formidable challenge to overcome. The presence of degrading enzymes, acidic pH conditions, and the gastrointestinal mucus layer pose significant barriers for genetic therapy, necessitating exploration of alternative therapeutic options. In recent years, transdermal and transpulmonary gene delivery modalities offer promising avenues with multiple advantages, such as non-invasion, avoided liver first-pass effect and improved patient compliance. Considering the rapid development of gene therapeutics via transdermal and transpulmonary administration, here we aim to summarize the nearest advances in transdermal and transpulmonary gene drug delivery. In this review, we firstly elaborate on current delivery carrier in gene therapy. We, further, describe approaches and applications for enhancing transdermal and transpulmonary gene delivery encompassing microneedles, chemical enhancers, physical methods for transdermal administration as well as nebulized formulations, dry powder formulations, and pressurized metered dose formulations for efficient transpulmonary delivery. Last but not least, the opportunities and outlooks of gene therapy through both administrated routes are highlighted.